1981
DOI: 10.1530/acta.0.0970338
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin content in rat pituitary gland. RIA of prolactin after different extraction procedures

Abstract: The prolactin content of rat pituitary varies considerably when determined by RIA, due to incomplete solubilization of prolactin secretory granules with standard procedures for tissue homogenization and centrifugation. Freezing and thawing, Triton X-100 and ultrasonic treatments increased the yield of prolactin significantly but electron microscopy of pellets revealed numerous unmodified secretory granules. Addition of 2.5 m urea produced complete extraction of tissue prolactin confirmed by RIA of supernatants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…Zanini and Giannattasio (1972) compared the efficiency of the extraction media by using electrophoresis and electron microscopy, concluding that 2.5 M urea completely solubilized PRL and GH, while water and phosphate buffer solubilized only a part of these hormones. Haggi and Aoki (1981) effect of urea, and further reported that F-T, sonication, or 1% triton X-100, though enhancing the efficiency of phosphate buffer, did not cause complete solubilization of PRL. In our previous report (Ishikawa et al, 1985), we demonstrated that PRL, which was solubilized with 0.25 M ammonium sulfate, pH 5.5, had isoelectric points quite different from those of PRL which remained in the residue and was solubilized with 60% EtOH pH 9.5.…”
Section: Stability Of Gh In 60% Etohmentioning
confidence: 92%
“…Zanini and Giannattasio (1972) compared the efficiency of the extraction media by using electrophoresis and electron microscopy, concluding that 2.5 M urea completely solubilized PRL and GH, while water and phosphate buffer solubilized only a part of these hormones. Haggi and Aoki (1981) effect of urea, and further reported that F-T, sonication, or 1% triton X-100, though enhancing the efficiency of phosphate buffer, did not cause complete solubilization of PRL. In our previous report (Ishikawa et al, 1985), we demonstrated that PRL, which was solubilized with 0.25 M ammonium sulfate, pH 5.5, had isoelectric points quite different from those of PRL which remained in the residue and was solubilized with 60% EtOH pH 9.5.…”
Section: Stability Of Gh In 60% Etohmentioning
confidence: 92%
“…It has been reported that some PRL present in the pituitary is not extracted into the supernatant when the pituitary is extracted by the common method with a homogenizer [10], and further, that secretory granules containing PRL particles are not disrupted in the buffer with isotonic solution [10,12,221. Therefore, the residue after Polytron extraction was disrupted with a Sonifier.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitaries were dissected, weighed and homogenized in 1 ml physiological saline containing urea (2.5 mol/l) and subjected to ultrasonic treatment (20). Samples were centrifuged for 20 min at 2800 g and the supernatant was frozen at 2 20 8C until analysis for hormone content.…”
Section: Hormone Assaysmentioning
confidence: 99%